Real-world impact of physical activity reward-driven digital app use on cardiometabolic and cardiovascular disease incidence - Adi Berliner Senderey; Tom Mushkat; Ofer Hadass; Daphna Carmeli; Samah Hayek; Marie-Laura Charpingnon; Eyal Jacobson; Ran D. Balicer (Communications Medicine)
Abstract Background The lack of effective tools available to health providers for enhancing patient physical activity prompts this study to examine the real-world impact of a physical activity reward-driven app on health outcomes, utilizing Electronic Health Records (EHR) data from Israel’s largest healthcare organization. Methods Conducting a retrospective cohort study, we matched app-users to non-users based on demographic and clinical characteristics. Results App-users have a significantly lower risk of cardiovascular disease (HR 0.95), stroke (HR 0.91), and type 2 diabetes (HR 0.82) compared to non-app users. Higher levels of physical activity among app users further reduce the incidence of cardiovascular disease (HR 0.87), stroke (HR 0.84), and type 2 diabetes (HR 0.75) compared with non-app user. However, engagement in mild physical activity, as measured by step count, does not differ from non- users in the incidence of these conditions. Conclusions These findings highlight the potential of app-based interventions to promote higher levels of physical activity and mitigate major vascular and metabolic illnesses.